2012
DOI: 10.1108/17465661211242804
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational health practices in Indian industries

Abstract: Purpose -The purpose of this paper is to assess the perceptions of safety officers on Occupational Health and Safety (OHS) norms extended to the workforce in Indian industries, understand implementation levels and find out deficiencies existing therein. Design/methodology/approach -In this study, the authors utilized factor analysis to develop an instrument specifically responsible for assessing OHS norms in three major industrial sectors through a broad-based questionnaire survey. The pattern of influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…According to some authors (Beriha, Patnaik & Mahapatra 2012;Hughes & Ferrett 2009), failure to adopt OHS standards and practices may negatively impact organisational performance, resulting in inter alia the loss of revenue, failure to retain business customers, low productivity, loss of investor confidence, demotivation and lack of commitment among employees. As seen from the study, some of these after-effects of poor OHS practices are already evident in black-owned SMEs in the construction industry.…”
Section: Theme 1: Occupational Health and Safetymentioning
confidence: 99%
“…According to some authors (Beriha, Patnaik & Mahapatra 2012;Hughes & Ferrett 2009), failure to adopt OHS standards and practices may negatively impact organisational performance, resulting in inter alia the loss of revenue, failure to retain business customers, low productivity, loss of investor confidence, demotivation and lack of commitment among employees. As seen from the study, some of these after-effects of poor OHS practices are already evident in black-owned SMEs in the construction industry.…”
Section: Theme 1: Occupational Health and Safetymentioning
confidence: 99%
“…The work of Aliabadi et al [45] predicted the hearing loss threshold in high-noise industrial workplaces in a steel factory, and analyzed the effects of occupational exposure risk factors on determining the hearing loss threshold. The work of Shankar Beriha et al [46] identified the deficiencies in safety health practices in Indian industries and analyzed the influence of workplace hazards on injury level and material damage. Other studies used ANNs to analyze and classify the risk of injury from machine and drilling [47], and the slip-trip incident risk in construction-related occupations [48].…”
Section: Artificial Neural Network In Occupational Safetymentioning
confidence: 99%
“…The items of safety performance were taken from the study of Beriha et al (2012). Responses were taken on a five-point likert scale ranging from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Safety Performance (Mediating Variable)mentioning
confidence: 99%
“…Occupational health and safety measures include legal imperative, ethical concerns, industrial relations, and financial performance (Beriha et al, 2012). Every organization should implement the occupational health and safety policies which will help in enhancing the performance of workers (Hinze, 1997).…”
Section: Introductionmentioning
confidence: 99%